Ответы и объяснения

Лучший Ответ!
2012-12-13T20:04:45+04:00

№1

а) (6-2x-6)/(x(x+3)=-2x/(x(x+3))=-2/(x+3)

б) 5b(a-b)(a+b)/(a(a-b)10b^2)=(a+b)/(2ab)

 

№2

(4x+4+5x-5)/20=1

9x=21

x=21/9=7/3

 

№3

2.3*10^9*3*10^-12=6.9*10^-3

0.006=6*10^-3

6.9*10^-3-6*10^-3=0.9*10^-3

6.9*10^-3/6*10^-3=1.15

(2.3*10^9)(3*10^-12) на 0.9*10^-3 и в 1.15 раз больше 0.006

 

№4

3*sqrt(2*8)/2=6

 

№5

6^12/(16^2*27^4)=6^12/(16^2*3^12)=2^12/2^8=2^4=16

 

№6

Возведем обе части в квадрат

(sqrt(45-20sqrt5)))^2=(5-2sqrt5)^2

45-20sqrt5=25-20sqrt5+20

45-20sqrt5=45-20sqrt5